New Insights in the Pathophysiology of Hospital- and Ventilator-Acquired Pneumonia: A Complex Interplay between Dysbiosis and Critical-Illness–Related Immunosuppression - Bourdiol, A.; Roquilly, A. (Seminars in Respiratory and Critical Care Medicine, 2022)
Both hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) have long been considered as diseases resulting from the invasion by pathogens of a previously sterile lung environment. Based on this historical understanding of their pathophysiology, our approaches for the prevention and treatment have significantly improved the outcomes of patients, but treatment failures remain frequent. Recent studies have suggested that the all-antimicrobial therapy-based treatment of pneumonia has reached a glass ceiling. The demonstration that the constant interactions between the respiratory microbiome and mucosal immunity are required to tune homeostasis in a state of symbiosis has changed our comprehension of pneumonia. We proposed that HAP and VAP should be considered as a state of dysbiosis, defined as the emergence of a dominant pathogen thriving at the same time from the catastrophic collapse of the fragile ecosystem of the lower respiratory tract and from the development of critical-illness–related immunosuppression. This multidimensional approach to the pathophysiology of HAP and VAP holds the potential to achieve future successes in research and critical care. Microbiome and mucosal immunity can indeed be manipulated and used as adjunctive therapies or targets to prevent or treat pneumonia.
Keywords: hospital-acquired pneumonia; dysbiosis; critical-illness–related immunosuppression